Saliva as a diagnostic tool in soccer: a scoping review - Ferreira, J; Jiménez, Manuel; Cerqueira, A; da Silva, GB; Souza, B; Berard, L; Bachi, ALL; Dame-Texeira, N; Coto, N; Heller, D (PeerJ, 2025)
Background: A high-performance sport like soccer requires training strategies that aim to reach peak performance at the right time for the desired competitions. Thus, the investigation of biochemical markers in saliva is a tool that is beginning to be used in athletes within the physical training process. There is still no evidence on universal saliva collection and analysis protocols in soccer. This review aims to map the use of saliva as a tool for analyzing athletic performance in soccer, from the biomarkers used to the validated protocols for these analyses. Methods: A broad systematic literature search was carried out in the electronic databases Web of Science, Livivo, Scopus, PubMed, LILACS and gray literature (Google Scholar and ProQuest). Two reviewers selected the studies and extracted data on the type of salivary collection used, the salivary biomarker evaluated and monitored. Results: Ninety-three articles were included. The most frequently analyzed salivary biomarkers were cortisol (n = 53), testosterone (n = 35), secretory immunoglobulin A (SIgA) (n = 33), salivary alpha amylase (n = 7), genetic polymorphisms (n = 4) and miRNAs (n = 2). The results of the studies indicated beneficial effects in monitoring salivary biomarkers in the assessment of sports performance, although most studies did not include a control group capable of comparison. Salivary collection and analysis protocols were varied and commonly not reported. Conclusions: This scoping review provides a comprehensive overview of the current landscape of salivary biomarker research in soccer. The findings underscore the importance of these biomarkers in assessing athletes' physiological responses and overall well-being. Future research should focus on refining methodologies, exploring additional biomarkers, and investigating the practical implications of salivary biomarker monitoring in soccer and other sports.
Keywords: biomarkers; saliva; salivary proteins and peptides; soccer; sports medicine